Upaya Pencegahan Obesitas untuk Pengendalian dan Pencegahan Penyakit Tidak Menular di Kelurahan Kenali Asama Bawah - Fatmawati, Tina Yuli; Nurfitriani, Nurfitriani; Ariyanto, Ariyanto; Efni, Nel; Rahmawati, Helfi (Universitas Baiturrahim, 2024)
Obesity is a multifactorial problem caused by genetic factors, environmental factors such as diet, sedentary lifestyle and physical activity. Obesity is closely related to the incidence of non-communicable Diseases (PTM) and causes death in 2.8 million adults each year. The purpose of this service is to increase public knowledge about Obesity Management in the Control and Prevention of Non-communicable Diseases. Dedication methods include lectures, discussions, simulations and anthropometric examinations. The activity was carried out in the Kenali Asam Bawah subdistrict with a total of 40 people. The results showed an increase in knowledge after providing education about obesity. In the pretest, 31 people (77.5%) had less knowledge, after being given education, community knowledge increased to 38 people (95%). To the public to maintain a healthy lifestyle by managing a healthy diet and doing physical activity/exercise every day as well as conducting regular general check-ups at health care facilities, so that health problems can be controlled early